Hydrogen–deuterium exchange mass spectrometry identifies spatially distinct antibody epitopes on domain III of the Zika virus envelope protein. (8th December 2020) - Adhikari, Jagat; Zhao, Haiyan; Fernandez, Estefania; Huang, Yining; Diamond, Michael S.; Fremont, Daved H.; Gross, Michael L.
Abstract: Zika virus (ZIKV) has become a global public health concern because it causes fetal microcephaly and other neurological complications in humans. Currently, there are no approved treatments or vaccines for ZIKV infection. We describe here the epitopes for six monoclonal antibodies (mAbs) that bind to domain III of the envelope protein of ZIKV, some of which have therapeutic potential. We show that by using hydrogen–deuterium exchange mass spectrometry (HDX‐MS), we can identify three spatially distinct epitopes for the six mAbs investigated. The HDX‐MS approach identified epitopes for three mAbs that agreed well with previously reported X‐ray crystallography data. The HDX‐MS determined epitopes for the other three anti‐ZIKV mAbs, for which there were no crystal structures, and the epitopes were confirmed by structure‐guided mutagenesis and biolayer interferometry competition binding assay. Our results have implications for the design of vaccine and antibody therapeutics against ZIKV and demonstrate the use of HDX‐MS as a rapid and valid approach for epitope mapping.